2018
DOI: 10.26442/terarkh201890848-52
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Arbidol in the prevention of virus-induced exacerbations of bronchial asthma and chronic obstructive pulmonary disease

Abstract: Aim. To assess the efficacy and safety of Arbidol in the influenza and ARVI preventing in patients with asthma and chronic obstructive pulmonary disease (COPD). Materials and methods. This study was an open label and prospective during epidemic period of 2016-2017 years. 100 outpatients aged 18 to 80 years with verified asthma and/or COPD, were enrolled to therapy group, and received oral umifenovir 200 mg once daily for 14 days and then 200 mg twice a week for 3 weeks.The medical records data for the same epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 1 publication
1
5
0
Order By: Relevance
“…A study of 100 patients with COPD or asthma found that seasonal and post-exposure prophylaxis using Arbidol (Umifenovir) was associated with 2.6-times reduction in influenza and acute respiratory viral infection related morbidity during an epidemic period. This study also showed that prophylactic administration of Arbidol before and during flu season reduced the frequency of infectious exacerbations of COPD [241].…”
Section: Sialic Acid (Sa) and Haemagglutinin A (Ha-a)supporting
confidence: 62%
“…A study of 100 patients with COPD or asthma found that seasonal and post-exposure prophylaxis using Arbidol (Umifenovir) was associated with 2.6-times reduction in influenza and acute respiratory viral infection related morbidity during an epidemic period. This study also showed that prophylactic administration of Arbidol before and during flu season reduced the frequency of infectious exacerbations of COPD [241].…”
Section: Sialic Acid (Sa) and Haemagglutinin A (Ha-a)supporting
confidence: 62%
“…A randomized controlled trial gave oral arbidol (200 mg/d) to workers during an influenza epidemic for 10 to 18 days and found that arbidol had significant preventative effects (12). Similarly, Titova et al administered oral arbidol to asthma and chronic obstructive pulmonary disease (COPD) patients to prevent viral infections (13). Recently, oral arbidol use indicated favorable clinical response in patients with COVID-19 (14).…”
Section: Discussionmentioning
confidence: 99%
“…Arbidol treatment coupled with lopinavir/ritonavir reckoned to retard the development of pulmonary lesions concurrently reducing the respiratory and gastrointestinal COVID-19 viral load thus lowering the transmission [132]. Encouragingly, seasonal prophylaxis with arbidol reduced influenza morbidity in patients with asthma and COPD during epidemic [133]. Four cases with mild to severe SARS-CoV2 pulmonary symptoms were subjected to antiviral therapy consisting of arbidol, lopinavir/ritonavir, and Shufeng Jiedu (traditional Chinese medicine) along with supportive care.…”
Section: Arbidolmentioning
confidence: 99%